STRUCTURE IDENTIFICATION OF A TRIMER STILBENOID COMPOUND FROM STEM BARK Hopea nigra (DIPTEROCARPACEAE) - Sri Atun; Nurfina Aznama; Retno Arianingrum; Masatake Niwab (Indonesian Journal of Chemistry, 2005)
Bioactivity as antihephatotoxic directed fractionation of aceton extract from the stem bark of Hopea nigra (Dipterocarpaceae) afforded a stilbenoid trimer, namely vaticanol G (1). The structure of this compound were elucidated based on physical and spectroscopic data (UV, IR, MS, 1H and 13C NMR 1D and 2D).